Influence of heteroaggregation processes between intrinsic colloids and carrier colloids on cerium(III) mobility through fractured carbonate rocks. (1st September 2016) - Tran, Emily; Klein Ben-David, Ofra; Teutch, Nadya; Weisbrod, Noam
Abstract: Colloid facilitated transport of radionuclides has been implicated as a major transport vector for leaked nuclear waste in the subsurface. Sorption of radionuclides onto mobile carrier colloids such as bentonite and humic acid often accelerates their transport through saturated rock fractures. Here, we employ column studies to investigate the impact of intrinsic, bentonite and humic acid colloids on the transport and recovery of Ce(III) through a fractured chalk core. Ce(III) recovery where either bentonite or humic colloids were added was 7.7–26.9% Ce for all experiments. Greater Ce(III) recovery was observed when both types of carrier colloids were present (25.4–37.4%). When only bentonite colloids were present, Ce(III) appeared to be fractionated between chemical sorption to the bentonite colloid surfaces and heteroaggregation of bentonite colloids with intrinsic carbonate colloids, precipitated naturally in solution. However, scanning electron microscope (SEM) images and colloid stability experiments reveal that in suspensions of humic acid colloids, colloid-facilitated Ce(III) migration results only from the latter attachment mechanism rather than from chemical sorption. This observed heteroaggregation of different colloid types may be an important factor to consider when predicting potential mobility of leaked radionuclides from geological repositories for spent fuel located in carbonate rocks. Graphical abstract: Highlights: Colloidal Ce migrates with or slightly faster than solutes. Greater recovery results from the presence of bentonite and humic acid colloids. Carbonate can precipitate with Ce to form intrinsic colloids. Intrinsic carbonate colloids heteroaggregate with carrier colloids. Heteroaggregates play an important role in Ce transport.